Treibhaus 6. - Kunstmuseum Düsseldorf (Düsseldorf : Kunstmuseum Düsseldorf, 1994)
Berg, Margarete ; Boje, Inken ; Haehnle, Enne ; Hoderlein, Stefan ; Höller, Stefan ; Hübner, Julia ; Kottmann, Norbert ; Landschreiber, Anke ; Lausch, Stefan ; Märtin, Peter ; Pfisterer, Anke ; Ratzke, Frauke ; etc.
Treibhaus 6, Kunstmuseum Düsseldorf, 11. September - 30. Oktober 1994
boek